Utilization of Evidence-Based Nursing Practice and Associated Factors Among Nurses Working in Saint Paul's Hospital Millennium Medical College, Ethiopia - Dinka Lamesa MSc; Wubareg Seifu MSc; Jabir Abdella MSc; Elias Ezo MSc (SAGE Publishing, 2023)
Introduction Organizations still struggle with the best mechanisms to implement research into practice, and guideline developers need to continue to strive toward collaboration and avoidance of duplication. Objective To assess the utilization of evidence-based nursing practice and associated factors among nurses working in Saint Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia, 2022. Methods An institutional-based cross-sectional study was conducted from 10 September 2022 to 25 November 2022. The total sample size was 418, and a simple random sampling technique was used to select nurses. Data were collected through a self-administered questionnaire. Data were entered using EpiData version 4.6 and exported to SPSS version 25 for analysis. Multicollinearity was considered by using a variance inflation factor (VIF > 10). The goodness of fit test was done using the Hosmer-Lemeshow model. Binary logistic regression was done, and variables with a p -value of less than 0.25 in the bivariable analysis were taken into the multivariable analysis. Statistical significance was declared at a p -value of less than 0.05 with an adjusted odds ratio and 95% confidence interval. Result The utilization of evidence-based nursing practice was 58.1% [95% CI: 52.23-63.24]. Male sex [AOR 4.65, 95%CI: 2.51-8.63], work experience of >5 years [AOR 6.83, 95%CI: 2.27-20.58], head nurse role in the hospital [AOR 1.72, 95%CI: 1.02-3.18], master's degree educational status [AOR 2.78, 95%CI: 1.89-8.61], and availability of EBNP guideline in the ward [AOR 1.24, 95%CI: 1.04-5.32] were significantly associated. Conclusion About six in 10 nurses utilize EBNP at Saint Paul's Hospital Millennium Medical College. Sex, experience of >5 years, head nurse role in the hospital, master's degree educational status, and availability of EBNP guidelines in the ward were significantly associated with the utilization of EBNP. Therefore, recruiting experienced nurses, learning master`s degrees, and availing the EBNP guidelines in the ward might increase the utilization of EBNP.